Ревизия рода Hyrcanana (Lepidoptera, Lycaenidae) - Некрутенко, Ю.П. (Вестник зоологии, 1983)
The paper contains redefinition of the genus Hyrcanana Bethune - Baker, 1914, and brief redescription of included species: H. caspia (Lederer, 1870), H, sultan (Lang, 1884), I. sartha (Staudinger, 1886) and H. evansi (de Nicéville, 1902). The rest of species assigned in the recent literature fo Hyrcanana, suggested to belong to Phoenicurusia Verity, 1943 and Athamanthia Zhdanko, 1983. The rank of the above generic taxa (generic vs. subgeneric within Lycaena F.) depends on a reviser's approach. Keys to genera and Hyrcanana species are given.
H. pamira sp. n. differs from H. sultan and H. caspia by tailless hindwings, from H. sartha and H. evansi by the absence of orange colour on the forewing underside, and by pure while fringe. Type locality: South-West Pamir, Tadjik SSR, Gorno-Badakhishanian Autonomous Region, Ishkashim, Nyut. Type maferial (30 males and 16
females) is deposited in the Zoological Museum of Kiev University (including holotype), Zoological Institute of the USSR Academy of Sciences (Leningrad) and in privale collection of V. A. Ganson (Moscow)